2005
DOI: 10.1007/s11178-005-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Heterocyclization into a Pyrazole System of Z-3-(2-Naphthyl)-3-chloro-2-propenal Semicarbazone and Thiosemicarbazone

Abstract: By reaction of Z-3-(2-naphthyl)-3-chloro-2-propenal with semicarbazide hydrochloride and thiosemicarbazide the corresponding semicarbazone and thiosemicarbazone were obtained that underwent a heterocyclization into a pyrazole system with elimination of amide moieties and with migration of the naphthyl fragment into the position 4 of the pyrazole ring. The alkylation of 4-(2-naphthyl)pyrazole synthesized with 2-nitropentachloro-1,3-butadiene afforded 1,1-bis[4-(2-naphthyl)-pyrazol-1-yl]-2-nitrotrichloro-1,3-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Due to its stepped reactivity, 2-nitroperchlorobuta-1,3-diene (1) has proved a valuable synthetic building block for heterocycles via S N Vin reactions. [1][2][3][4] Substitution with two equivalents of primary N-nucleophiles such as aniline and its electron-rich derivatives 2 (ERG = electron-releasing group) leads to the formation of ketene aminals 3, probably via the corresponding amidines. 5 On the contrary, during reaction with electron deficient anilines 4 (EWG = electron-withdrawing group) such as 4-nitroaniline a different reaction channel is opened instead after the first N-substitution, leading to allylidene arylhydrazines 5 (Scheme 1).…”
mentioning
confidence: 99%
“…Due to its stepped reactivity, 2-nitroperchlorobuta-1,3-diene (1) has proved a valuable synthetic building block for heterocycles via S N Vin reactions. [1][2][3][4] Substitution with two equivalents of primary N-nucleophiles such as aniline and its electron-rich derivatives 2 (ERG = electron-releasing group) leads to the formation of ketene aminals 3, probably via the corresponding amidines. 5 On the contrary, during reaction with electron deficient anilines 4 (EWG = electron-withdrawing group) such as 4-nitroaniline a different reaction channel is opened instead after the first N-substitution, leading to allylidene arylhydrazines 5 (Scheme 1).…”
mentioning
confidence: 99%
“…Substituted 2‐alkenals 66 , which contained an easily eliminated nucleophilic group at the 3‐position, have been employed as a scaffold for the construction of pyrazoles ,. Over the past 10 years, it has been shown that the reaction of 3‐dimethylamino‐5‐(trimethyl‐2‐cyclohexen‐1‐yl)‐2,4‐pentadienal ( 66 a ) or 3‐chloro‐3‐(2‐naphthyl)‐propenal ( 66 b ) with hydrazine hydrate ( 67 c ) readily furnishes the corresponding 1H‐pyrazoles ( 69 ) in 89 and 74 % yield, respectively. The reaction proceeds through a hydrazone intermediate ( 68 ), which cyclizes by nucleophilic vinyl substitution of the chlorine atom or the dimethylamino moiety.…”
Section: Pyrazoles Pyrazolines and Pyrazolidinesmentioning
confidence: 99%